Strategi Pemulihan Sektor Pariwisata Dan Ekonomi Kreatif Masa Pandemi Covid-19 - Elpa Hermawan (Universitas Hamzanwadi, 2021)
The Covid-19 pandemic has had a major impact on the sustainability of the tourism sector and the creative economy in Indonesia. Tourism activities around the world have also been temporarily suspended. The purpose of this study was to determine the recovery strategy of the tourism sector and the creative economy from the Ministry during the COVID-19 pandemic. The method used is descriptive qualitative. The data is taken from the results of the year-end press conference and webinars from the Creative Economy Marketing Director. Data analysis consisted of data reduction, data presentation and conclusion drawing. The results of the study conclude that several programs launched in the context of restoring the tourism sector and the creative economy are Indonesia Care, Certified CHSE, Grants, and Local Creative Purchases. The Ministry of Tourism and Creative Economy also launched 3 program platforms, namely innovation, adaptation, and collaboration. The implication of this research is to provide an in-depth understanding that the Ministry of Tourism and Creative Economy always has a long-term and short-term orientation in restoring the tourism sector and the creative economy during the pandemic or post-covid-19 pandemic. The various programs launched have involved all parties such as local governments, tourist destination managers, the private sector, or entrepreneurs and business actors in the tourism world.